2010
DOI: 10.2528/pierb10072808
|View full text |Cite
|
Sign up to set email alerts
|

How Lightning Tortuosity Affects the Electromagnetic Fields by Augmenting Their Effective Distance

Abstract: Abstract-A novel approach for developing the electromagnetic fields from a lightning return stroke which follows a tortuous path will be presented. The proposed model is unique in that it recognizes that the symmetrical tortuosity of lightning directly impacts the observable distance r, which in turn, alters the resulting electromagnetic fields. In the literature, lightning return stroke models typically employ the assumption that the cloud-to-ground path is straight. Although this assumption yields fairly con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…When the electric field distribution generated by the opposite charges reaches a critical value, the insulating capacity of the air breaks down, generating the lightning discharge. Many studies have investigated on the effect of the LEMP due to the characteristics of the lightning channel, such as its inclination [59,60] and, more recently, its tortuosity [61][62][63]. LC tortuosity can significantly affect the generated fields and consequently the induced voltages.…”
Section: Geometrical Model Of the Lightning-channelmentioning
confidence: 99%
“…When the electric field distribution generated by the opposite charges reaches a critical value, the insulating capacity of the air breaks down, generating the lightning discharge. Many studies have investigated on the effect of the LEMP due to the characteristics of the lightning channel, such as its inclination [59,60] and, more recently, its tortuosity [61][62][63]. LC tortuosity can significantly affect the generated fields and consequently the induced voltages.…”
Section: Geometrical Model Of the Lightning-channelmentioning
confidence: 99%
“…The effects on naval systems by induced voltages due to channel tortuosity, horizontal parts and other complexities of the channel, branch currents, etc. should be further studied in detail by applying recently developed sophisticated models [49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Cooray and Lundquist (1985) considered that the fine structure on the E‐field waveform is caused by sudden changes in the channel current, channel geometry, or RS velocity. Similarly, many of the fine, microsecond‐scale structures in the E‐field waveform can be attributed to the tortuous channel (Le Vine & Willett, 1995; Meredith et al., 2010; Willett et al., 2008), Shao et al. (2012) suggested that the kink of the fine structure on the E‐field waveform can be caused by the dispersive and lossy current propagation in the RS channel.…”
Section: Introductionmentioning
confidence: 99%